2014
DOI: 10.1097/mpg.0000000000000409
|View full text |Cite
|
Sign up to set email alerts
|

Liver Enzyme Elevations Within 3 Months of Diagnosis of Inflammatory Bowel Disease and Likelihood of Liver Disease

Abstract: Elevation of both ALT and GGT within 90 days after the diagnosis of IBD is associated with a markedly increased likelihood of IBD-LD. Both ALT and GGT levels should be measured in all of the pediatric patients newly diagnosed as having IBD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
16
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 8 publications
0
16
1
Order By: Relevance
“…15 most helpful diagnostic tool in the identification of IBD-associated AILD. 30 In 4% of cases liver enzymes were normal at the time of AILD diagnosis but hepatobiliary abnormalities were found at imaging.…”
Section: Discussionmentioning
confidence: 97%
“…15 most helpful diagnostic tool in the identification of IBD-associated AILD. 30 In 4% of cases liver enzymes were normal at the time of AILD diagnosis but hepatobiliary abnormalities were found at imaging.…”
Section: Discussionmentioning
confidence: 97%
“…Although numerous studies about hepatobiliary manifestations in inflammatory bowel disease (IBD) in adults have been published, data concerning the pediatric population are still insufficient. The diagnosis of hepatic disorders often starts with abnormal liver enzyme tests, which have been found in up to 40% of pediatric patients with IBD [1-3]. The association between an increased likelihood of IBD-liver disease and elevation of alanine aminotransferase (ALT) and glutamyl transpeptidase (GGT) activities within 90 days’ follow-up after the diagnosis of IBD was reported [3].…”
Section: Introductionmentioning
confidence: 99%
“…The Pediatric IBD Collaborative Research Group Registry recently reported significant associations between elevated LEs at the time of IBD diagnosis and chronic liver disease. 9 However, this study was limited to only an evaluation of LEs in the first 3 months after IBD diagnosis.…”
mentioning
confidence: 99%